If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 7p = 6p Solving 12 + 7p = 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 12 + 7p + -6p = 6p + -6p Combine like terms: 7p + -6p = 1p 12 + 1p = 6p + -6p Combine like terms: 6p + -6p = 0 12 + 1p = 0 Add '-12' to each side of the equation. 12 + -12 + 1p = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 1p = 0 + -12 1p = 0 + -12 Combine like terms: 0 + -12 = -12 1p = -12 Divide each side by '1'. p = -12 Simplifying p = -12
| 22+2x=3x-8 | | 0.25w-3.09=0.75w+8 | | x=180-12y | | x+.15x=2852 | | -2+3x=5x+6 | | 8x+3=2+9 | | 14-5q=3q | | 3(-4+n)=16-n | | 10=(x)25 | | 5(1+4b)=2(3+10b) | | 2(2x-10)-8=(14-3x) | | 7a-5=-2 | | 0.2x-3.4=7.2 | | 4u-11=45 | | 23y+30=16 | | 13x+41=3x+5 | | 6x-5=-59 | | 12=2y-4x | | 3x^2+2xy+y^2=68 | | 4(8-9)+5= | | 4(8-9k)+5= | | 23y=-14 | | 8w=17 | | 24p+64=0 | | 0.15m+10=14.50 | | 7+40x=2 | | 20+90+y=180 | | 13x+2y=19 | | 16-27=x | | 3f-12=-2 | | -5(4y-1)+6y=19 | | Y=.10+5 |